Visible‐Light‐Induced Aerobic Oxidative Csp3−H Functionalization of Glycine Derivatives for 2‐Substituted Benzoxazoles. Issue 10 (26th March 2021) - Zhu, Zhi‐Qiang; Liu, Shan; Hu, Zhi‐Yu; Xie, Zong‐Bo; Tang, Juan; Le, Zhang‐Gao
Abstract: We report a simple oxidative C sp 3 −H functionalization reaction of glycine derivatives by visible‐light photoredox catalysis. A wide range of glycine derivatives readily undergo the oxidative cyclization to afford various 2‐substituted benzoxazoles. Importantly, this photocatalytic intramolecular dehydrogenative coupling reaction allows for the C−H functionalization of glycine derivatives involving short peptides under mild conditions, which may have value in preparing peptide‐derived pharmacologically active molecules. Abstract :